Dendritic spine anomalies and PTEN alterations in a mouse model of VPA-induced autism spectrum disorder. (February 2018) - Mahmood, Usman; Ahn, Sangzin; Yang, Eun-Jeong; Choi, Moonseok; Kim, Hyunju; Regan, Philip; Cho, Kwangwook; Kim, Hye-Sun
Graphical abstract: Abstract: Mounting evidence suggests that the etiology of autism spectrum disorders (ASDs) is profoundly influenced by exposure to environmental factors, although the precise molecular and cellular links remain ill-defined. In this study, we examined how exposure to valproic acid (VPA) during pregnancy is associated with an increased incidence of ASD. A mouse model was established by injecting VPA at embryonic day 13, and its behavioral phenotypes including impaired social interaction, increased repetitive behaviors and decreased nociception were observed at postnatal days 21–42. VPA-treated mice showed dysregulation of synaptic structure in cortical neurons, including a reduced proportion of filopodium-type and stubby spines and increased proportions of thin and mushroom-type spines, along with a decreased spine head size. We also found that VPA-treatment led to decreased expression of phosphate and tensin homolog (PTEN) and increased levels of p -AKT protein in the hippocampus and cortex. Our data suggest that there is a correlation between VPA exposure and dysregulation of PTEN with ASD-like behavioral and neuroanatomical changes, and this may be a potential mechanism of VPA-induced ASD.